P234 Characterisation of human synovial tissue dendritic cells in rheumatoid arthritis patients. (20th April 2020) - Elmesmari, Aziza; MacDonald, Lucy; Vaughan, Diane; Tolusso, Barbara; Bui, Laura; Gigante, Maria Rita; Federico, Francesco; Ferraccioli, Gianfranco; Gremese, Elisa; McInnes, Iain B; Alivernini, Stefano; Kurowska-Stolarska, Mariola
Abstract: Background: Dendritic cells (DCs) direct immune responses against pathogens while maintaining tolerance to self-antigens. However, their aberrant activation can lead to autoimmunity and inflammation. DCs consist of two subtypes: plasmacytoid and myeloid DCs. Recently, single-cell sequencing has revealed complex heterogeneity within myeloid DCs. These cells can be divided into CD141 pos (DC1), DC2 defined as CD1 high CD163 neg and DC3 defined as CD1c low CD163 high . In addition, a population of CD1c neg CD141 neg CD16 pos (DC4), which share some gene expression with CD16 pos monocytes, has been identified. To date, most studies of RA investigated DC precursors in circulation or synovial fluid (SF). However, DCs perform their functions within lymphoid or peripheral tissue. Therefore, in this study, we sought to characterise myeloid DC subsets in synovial tissue (ST) with the prospect of better understanding their role in driving autoimmunity in RA. Methods: We developed a flow sorting strategy to characterise the phenotype of distinct myeloid DC subsets in multiple biological compartments (PB, SF, and ST). Ultrasound-guided ST biopsies (RA n = 9; Psoriatic arthritis n = 3 with active disease) were digested with liberase prior to analysis. PB DCs (RA n = 19, Psoriatic arthritis n = 16, healthy donors n = 12), and SF DC (n = 3) were used as comparators. ST, SF and PB DCs were sorted then microRNA, pro-inflammatory and regulatory cytokine expression analysed by amplified qPCR. To evaluate the role of miR-155 in RA CD1c pos DC activation, CD1c pos cells were computationally sub-setted from a scRNAseq synovial dataset comparing synovial tissues of healthy individuals (n = 4) with patients with active RA (n = 7) and those in sustained clinical and ultrasound remission (n = 7). To elucidate the role of miR-155, CD1c pos DC from RA patients (n = 10) were sorted then transfected with miR-155 mimic or control mimic and the cytokines expression and produced were evaluated using quantitative RT-PCR and Luminex, respectively. Results: Our data revealed that whilst all myeloid DCs subsets can be present in inflamed RA synovium they occur with variable frequencies. CD1c pos (DC2/3) being the most abundant, followed by CD16 pos DCs (DC4), whilst CD141 pos DCs (DC1) occur in low numbers or are absent. CD1c pos DC sorted from RA ST express high levels of epigenetic regulators of inflammatory response miR-155, IL-6, TNF-a and IL-23 as compared to circulating cells.Unsupervised clustering of synovial CD1c cells identified 4 separate clusters including a distinctive miR155 positive CD1c cluster in RA patients. These cells showed significantly higher expression of pro-inflammatory cytokines and co-stimulatory molecules compared to other synovial CD1c clusters. Overexpression of miR-155 in CD1c pos leads to increased production of TNF-a and IL-23. Conclusion: Our data show that miR-155 is strongly implicated as an epigenetic regulator of the pro-inflammatory synovial CD1c pos DCs sub-cluster and contributes to exacerbating RA. Disclosures: A. Elmesmari None. L. MacDonald None. D. Vaughan None. B. Tolusso None. L. Bui None. M. Gigante None. F. Federico None. G. Ferraccioli None. E. Gremese None. I. B McInnes None. S. Alivernini None. M. Kurowska-Stolarska None.